PTU-177 Diabetic gastroparesis- a review of clinical practice in county durham. (22nd June 2015) - Aldibbiat, A; Nash, E; Sinclair, C; Praveen, P; Peter, P; Dhar, A
Abstract : Introduction: Diabetic gastroparesis represents a significant health burden not only for patients and their families but also for health care systems. 1 Treatment guidelines for gastroparesis are limited 2 and evidence base for effectiveness of current treatment modalities is lacking. Method: This study aims to evaluate patients with diabetic gastroparesis, assess disease burden and response to therapy. The diabetes database was used to identify patients, epidemiological and clinical data acquired from electronic pt records. A quality of life index 3 (QoLI) and Gastroparesis Cardinal Symptom Index 4 (GPCSI) questionnaire was completed. Results: 40 pts identified but 7 excluded due to moving away (5), not consenting for participation (1) or dying (1). Median age 48 yrs (21–85), 61% female. 73% had Type 1 diabetes mellitus, duration of diabetes 18 yrs (2–53). BMI = 26.7 (16.2–40) kg/m 2 . 39% nonsmokers, 21% current smokers. 82% of patients had one or more diabetes related complications. Median duration of diabetes before diagnosis 11.5 yrs (0–43). The cohort had 65 hospital admissions in the preceding 12 mths, median of 1 (0–15) per pt. 332 outpatient clinic visits were recorded. In those with T1DM, 33% had subcutaneous insulin infusion (CSII), while 67% of those with T2DM were receiving insulin. Diabetes was stable in 30% of pts. Nausea and vomiting were the most prominent symptoms in 97% of patients. Other symptoms included bloating (61%), early satiety (30%), constipation (33%) and diarrhoea (21%). Diagnosis was confirmed by scintigraphic single phase solid meal gastric emptying studies in 88%. 64% adopted life style modifications with 43% reporting sustained benefit. Prokinetic medications tried included: metoclopramide (58%), domperidone (76%), prochlorperazine (12%) and erythromycin (33%) with less than half of patients experiencing lasting benefit. Prucalopride was used in 11%. Pyloric injection with Botulinum toxin A was carried out in 15% with 20% reporting lasting benefit. Gastric electric stimulator was inserted in 8 (24%) patients 2 of whom had maintained benefit while rest of patients lost benefit within few month of device insertion. Surgical procedures were required in 3 (9%) pts. QoLi and GPCSI scores showed no correlation with glycaemic control or diabetes stability. Conclusion: Diabetic patients with gastroparesis have increased health needs and multiple complications. Majority of treatments have only transient benefit, which tend to wane off. There was no correlation between duration of diabetes, diabetes control or diabetes stability and QoLI or GPCSI scores. A multi disciplinary appraoch is needed to manage these patients and new treatments need to be developed for long term benefits. Disclosure of interest: A. Aldibbiat: None Declared, E. Nash: None Declared, C. Sinclair: None Declared, P. Praveen: None Declared, P. Peter: None Declared, A. Dhar Grant/ Research Support from: Carefusion UK, Consultant for: Takeda Pharmaceuticals, Speaker Bureau of: Falk Pharmaceuticals, Covidien.